2015
DOI: 10.1002/jps.24182
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles for Drug Delivery via the Gastrointestinal Tract

Abstract: Both patients and physicians prefer the oral route of drug delivery. The gastrointestinal (GI) tract, though, limits the bioavailability of certain therapeutics because of its protease and bacteria-rich environment as well as general pH variability from pH 1–7. These extreme environments make oral delivery particularly challenging for the biologic class of therapeutics. Here we demonstrate proof-of-concept experiments in swine that microneedle-based delivery has the capacity for improved bioavailability of a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 20 publications
(25 reference statements)
1
97
0
Order By: Relevance
“…39 Although ABS is not bioresorbable, it can potentially be used in pharmaceutical applications due to its biocompatibility and strong chemical resistance, and thus it can be passed out of the body safely, as with most foreign bodies. 40 However, more studies should be performed to address the ongoing concerns about the possible leaching of acrylonitrile monomers, which may be carcinogenic. 41 Other than ABS, various polymers have also been utilized in the pharmaceutical industry for the 3D printing of drug delivery systems using the FDM technique.…”
Section: Limitationsmentioning
confidence: 99%
“…39 Although ABS is not bioresorbable, it can potentially be used in pharmaceutical applications due to its biocompatibility and strong chemical resistance, and thus it can be passed out of the body safely, as with most foreign bodies. 40 However, more studies should be performed to address the ongoing concerns about the possible leaching of acrylonitrile monomers, which may be carcinogenic. 41 Other than ABS, various polymers have also been utilized in the pharmaceutical industry for the 3D printing of drug delivery systems using the FDM technique.…”
Section: Limitationsmentioning
confidence: 99%
“…By increasing surface area, micro- and nanofeatures increase the interfacial surface adhesion [6467]. Cylindrical pills coated with microneedles designed for physical penetration of epithelial tissue to increase drug permeation are also likely to provide the additional benefit of increased adhesion to the GI tract [68]. As with asymmetric surface functionalization, asymmetric topographical modifications have potential to promote unidirectional drug release toward epithelial tissue.…”
Section: Strategies To Increase Micro/nanofabricated Oral Drug Delmentioning
confidence: 99%
“…While microneedles have been more widely explored in drug delivery across the skin, the idea of physically puncturing GI tissue using microneedle pills have been recently presented in the field [68]. This proof-of-concept study showed safety and feasibility in evaluation of the prototype in vivo by delivering insulin through the oral route.…”
Section: Epithelial Permeation Enhancementmentioning
confidence: 99%
“…Massachusetts Institute of Technology (MIT) researchers reported on a similar device, also capable of potentially delivering peptides including insulin and tested in pigs. Instead of sugar, their "needle pill" used stainless steel that was gradually exposed as pH levels in the digestive system wore off the capsule's outer layer [132]. It will be interesting to see if such designs can be scaled for man and more importantly, if they can negotiate the extensive toxicology questions raised by such a direct interaction with the intestinal wall.…”
Section: Microneedle Approachesmentioning
confidence: 99%